The Philosophy underlying the person-of-the-therapist training model - Harry Aponte (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The "Person-of the-Therapist" model is an approach to training and supervising therapists. The concept of a therapist as a wounded healer appears to be key in interpreting the therapeutic process and its healing power. This article aims at presenting this model's philosophical foundations, which promote a creative use of the therapists' personal potential independently of the different psychotherapeutic schools that they represent.